STUDY ON MECHANICAL BEHAVIOR ANALYSIS AND OPTIMIZATION OF STIFFENED RIBBED PLATE (MT) - ZHANG ChenFan; DENG QingTian; LI XinBo; HOU ZhaoYang (Jixie qiangdu)
Using finite element simulation and experimental testing methods, with three stiffened rib configurations as the research object, the effect of the stiffened rib configuration on the mechanical behavior of the stiffened plate structure is analyzed under the given material parameters and geometric parameters of the stiffened plate. And the method of sine curve instead of straight line is used to optimize the structure. The research shows that the reinforcement effect of the plate is better than the positive distribution when the square configuration is distributed in the 45° direction, and the vertical distribution of the regular hexagon and the inner concave configuration has better plate reinforcement effect than the horizontal distribution and the 45° direction distribution; the smaller the angle between the pores of the stiffened configuration is, the better the reinforcement effect of the plate is; the use of sinusoids in the stiffened layer instead of the straight line boundary can significantly improve the bearing capacity of the stiffened plate; through the analysis of the crack path of the stiffened plate, it can be obtained that all the stiffened layers of the stiffened plate expand along the longitudinal rib wall at the load-bearing position after bending and deformation.